Quantitative assessment of the high-light tolerance in plants with an impaired photosystem II donor side. Issue 9 (15th May 2019) - Wilson, Sam; Ruban, Alexander V.
Abstract : Photoinhibition is the light-induced down-regulation of photosynthetic efficiency, the primary target of which is photosystem II (PSII). Currently, there is no clear consensus on the exact mechanism of this process. However, it is clear that inhibition can occur through limitations on both the acceptor- and donor side of PSII. The former mechanism is caused by electron transport limitations at the PSII acceptor side. Whilst, the latter mechanism relies on the disruption of the oxygen-evolving complex. Both of these mechanisms damage the PSII reaction centre (RC). Using a novel chlorophyll fluorescence methodology, RC photoinactivation can be sensitively measured and quantified alongside photoprotection in vivo . This is achieved through estimation of the redox state of Q A, using the parameter of photochemical quenching in the dark (qPd). This study shows that through the use of PSII donor-side inhibitors, such as UV-B and Cd 2+, there is a steeper gradient of photoinactivation in the systems with a weakened donor side, independent of the level of NPQ attained. This is coupled with a concomitant decline in the light tolerance of PSII. The native light tolerance is partially restored upon the use of 1, 5-diphenylcarbazide (DPC), a PSII electron donor, allowing for the balance between the inhibitory pathways to be sensitively quantified. Thus, this study confirms that the impact of donor-side inhibition can be detected alongside acceptor-side photoinhibition using the qPd parameter and confirms qPd as a valid, sensitive and unambiguous parameter to sensitively quantify the onset of photoinhibition through both acceptor- or donor-side mechanisms.